Kriteria Kemaqbulan Hadis Oleh Aisyah Dan Pengaruhnya Terhadap Pemahaman Hadis - Eko Seprianto (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This study aims to reveal the various criteria used to determine the status of the abstinence of hadith by Aisyah and the effect of these criteria on the understanding of hadith in the next era. The method used is content analysis with the fiqh hadith approach. The primary data used is the work of Imam al-Zarkasyi entitled al-Ijaabah Liiraadi Mastadrakathu 'Aaisyah' Ala Shahaabah. The results show that the criteria for the abstinence of hadith according to Aisyah are not against the Qur'an and well-known traditions and are not against logic. The effect of these criteria for abstinence on the understanding of hadith also varies. Abu Hanifah and scholar Ahnaf accepted these criteria and used them in understanding the hadith. Meanwhile, Imam al-Syafi'i and ulama Syafi'iyah seem to use another way to accept a hadith.